Implementasi Pembelajaran Berdiferensiasi pada Mata Pelajaran Pendidikan Pancasila di SDN Jatinegara Kaum 06 - Nadifha Nisrina Putri Ridwan (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2026)
This study aims to describe the experiences of mover teachers and nonmover teachers in understanding, planning, and implementing differentiated instruction in Pancasila Education at SDN Jatinegara Kaum 06. This study uses a qualitative phenomenological approach with data collection techniques in the form of observation, interviews, and documentation, as well as Miles and Huberman data analysis. The results show that the implementation of differentiated instruction by mover and nonmover teachers is dynamic, evolving, and adaptive. Mover teachers already have a conceptual understanding of differentiated instruction, but its application is still situational and inconsistent. Meanwhile, nonmover teachers initially had limited understanding, but showed development through direct experience, discussions with colleagues, and observation of student responses. In terms of planning and implementation, the differences between mover and nonmover teachers narrowed, with the most noticeable differentiation in group activities and learning task variations. Thus, differentiated instruction in the context of Pancasila Education is not determined by the status of teachers as mover or nonmover, but develops gradually and continuously through teachers' experiences, reflections, and adjustments to the dynamics of learning in the classroom.